2019
DOI: 10.31557/apjcp.2019.20.2.495
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Intestinal Parasitic Infection in Cancer, Organ Transplant and Primary Immunodeficiency Patients in Tehran, Iran

Abstract: Background:Intestinal parasitic infection in immunodeficient patients especially those with impaired cellular immunity, like neoplasia, renal or heart transplant needs careful consideration. The objective of this study is to evaluate the prevalence of intestinal parasites in different group of patients including cancer patients; organ transplants recipients, and primary immunodeficiency patients.Methods:Stool samples from 190 patients including 80 patients with Primary Immunodeficiency, 85 cancer patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
20
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 41 publications
2
20
1
1
Order By: Relevance
“…However, the results of several studies conducted in Iran showed that the prevalence of intestinal parasite infections among cancer patients under chemotherapy varies from 4.16% to 35.9%. 5,18,[24][25][26][27][28][29] On the other hand, the current widespread use of chemotherapy has altered the pattern of some parasitic infections so as they have become one of the most important causes of the global risk of health and probably the cause of an increase in the rate of morbidity and mortality in immunocompromised patients. 30,31 This crosssectional descriptive study assessed the epidemiological state of intestinal parasitic infections among cancer patients undergoing chemotherapy in Shahrekord, Iran.…”
Section: Discussionmentioning
confidence: 99%
“…However, the results of several studies conducted in Iran showed that the prevalence of intestinal parasite infections among cancer patients under chemotherapy varies from 4.16% to 35.9%. 5,18,[24][25][26][27][28][29] On the other hand, the current widespread use of chemotherapy has altered the pattern of some parasitic infections so as they have become one of the most important causes of the global risk of health and probably the cause of an increase in the rate of morbidity and mortality in immunocompromised patients. 30,31 This crosssectional descriptive study assessed the epidemiological state of intestinal parasitic infections among cancer patients undergoing chemotherapy in Shahrekord, Iran.…”
Section: Discussionmentioning
confidence: 99%
“…Other extra intestinal diseases, such as urticaria, chronic angioedema, anaemia, chronic liver disease and reactive arthritis have also been reported to be potentially associated with Blastocystis infection [14,15,16,17,18]. Blastocystis has also been reported to have an opportunistic role in immunocompromised individuals (cancer, organ transplant and human immunodeficiency virus patients) [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…They also showed that Cryptosporidium spp. was the primary cause of parasitic intestinal infection in patients with organ transplant (20%) compared to primary immunodeficiency patients (1.25%) [ 26 ]. As the previous studies have shown, our results have also shown that children affected by malignancies and under treatment by chemotherapy are highly prone to parasitic infections, and it could be due to their effects on immunity mechanisms that include a mucosal membrane, skin, quantitative and qualitative defect of granulocytes, and macrophages.…”
Section: Discussionmentioning
confidence: 99%